Do international portfolio investors follow firms' foreign investment decisions? - Roberto A. De Santis; Paul Ehling (European Central Bank (ECB), 2007)
We analyze the interlinkages between foreign direct investment (FDI) and foreign portfolio investment (FPI) between Germany and the major economies. First, we show that Tobin's q helps explaining the variation of the growth rate of the stock of FDI. Second, we show that foreign and the home stock market returns explain the ariation of the growth rate of the stock of FPI. Most importantly, we find that information about foreign fundamentals is revealed via direct investment. In other words, FDI transactions measured by fitted growth rates of the stock of FDI help explaining current growth rates of the stock of FPI. To our knowledge this observation is the first unambiguous evidence that international portfolio investors follow firms' expected foreign investment decisions.
Keywords: F21; F23; G11; G15; 330; and Information Spillovers; Foreign Direct Investment; Foreign Portfolio Investment; Investor Heterogeneity; Tobin's q; Auslandsinvestition; Portfolio-Investition; Tobins Q; Deutschland; Industrieländer